Emergency Medicine and Rapid Response Virtual Team (EM-RRVT): Insights from the Hajj 1445/2025 Experience - Sharafaldeen Bin Nafisah; Abdullah Mohammed Alhutrushi; Atheer Abdullah Abanmi; Mohammed Hassan Abujamous; Loay Hammad Sabbah; Layla Sulaiman AlSalehi; Ziyad Khater Alzahrani; Abdullah Abdulaziz Alwabel; Abdulaziz Suliman Alhomod; Mona Sahman Alsubaie (The Journal of Medicine, Law & Public Health)
Introduction: The use of telemedicine in acute care settings has not been investigated in large mass gatherings. Further exploration is needed to determine its efficacy, applicability and to explore challenges and opportunities.